Modern trends in development of artificial joints for human (literature review) - Filipenko, Volodymyr; Tankut, Volodymyr; Melnyk-Kahliak, N.; Kosiakov, Oleksandr; Sokhan, Sergiy (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2017)
<span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: ’Times New Roman’; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">Total hip replacement due to its effectiveness is the most common treatment for patients with severe diseases of the joints. The modern idea of the choice of materials (and methods of their application as a pair of friction) for the replacement of large joints are described, set the scope of the problems and possible their solutions. We characterize some directions of improvement of artificial human joints. It was emphasized that so far there is no perfect pair of friction in artificial joints, and it determines the choice of the surgeon, taking into account the anatomical and physiological state of the patients joint. The search continues for ways to improve the mechanical, tribological and biological properties of friction pairs in artificial joints based on the creation of ceramic, plastic, sapphire and composite materials with new properties. However, the full potential of the developed polymer composites, carbon nanotubes, graphene needs in-depth study of their cytotoxicity, which to date is a matter of debate. Based on the analysis of trends in the field of materials for friction pairs in joint endoprostheses, the authors identified two major technological trends for the near future. First, it is the development of structure-hardened surface layer with a low coefficient of friction (ie. natural oxide films instead of coating) on the metal components. Secondly, it can be the development of new ceramic shock-viscous materials with minimized risk for crack formation in the ceramic-ceramic joints.